Examining the Link Between Identity Management and Object Recognition in Contemporary Trading Markets in Education Using AI - Saba, Nihale; Krit, Salahddine (European Journal of Applied Sciences, 2026)
This study looks at how identity management and object recognition work together in the newest trading markets. Our main focus is education. AI, or artificial intelligence, is now common in a lot of areas, like trading. We want to find out how better identity management can help with recognizing objects. This change can help people make better decisions in educational trading settings. AI has changed how schools do trading simulations and market analysis. It's important to control who can see what tools and data. This is done by managing identities. Recognizing objects is also very important. It helps you see and understand signals in the market. This article will go into detail about how these two work together. It wants to show how they make trading strategies better in schools.